Problema Pengembangan Moral Remaja dalam Perspektif Pendidikan Islam - Hidajah, Siti Hidjatul (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2012)
Islamic education is basically a process of creating human being who is continue, oriented and planned in order to have future generation who is faithful, smart, and even skillful, improving manner and attitude, strengthening personality, and promoting spirit of nation so that it can create humans who can develop their own selves, and collectively responsible of national development. Therefore, two kinds of education, central which basically focus on forming inner heart which emphasize on character, attitude, and personality that responsible of moral, social and religious life; real mature human with peripheral education, human effort to have children maturity with cultural life, to make human in social and cultural aspects need to be well synergized. It does not mean both kind of education cannot meet in one point in order to have ideal human, human who is smart, skillful, and faithful based on the underlying philosophy of our states.